Prototipe Virtual Tour Campus Menggunakan Metode 360 Degree Panning - Satya Arisena Hendrawan; Diky Wardhani (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
The benefits of using the internet to find articles or information can be easily accessed by anyone in various circles. In the field of information technology, many different ways of processing data, both in the form of text, images and sound, are developed using various interactive visual methods. So that it changes the presentation of information delivery used to stimulate thoughts, feelings, attention and knowledge that is more than the information presented (Suryani et al. 2018). This became the basis for research and changed the delivery of information about the BRI Institute campus and introduced it to the public in the form of a 360 panoramic image. This research uses the Multimedia Development Life Cycle method.